Prenatal exposure of extra vitamin D from fortification and later risk of inflammatory bowel disease. (13th November 2019) - Duus, K S; Moos, C M; Frederiksen, P; Andersen, V; Heitmann, B L
Abstract: Introduction: Inflammatory bowel disease (IBD) is a chronic immune-mediated inflammatory disease that can affect the entire digestive tract. Approximately 1% of the Danish population has IBD today. Both the incidence and prevalence of IBD are increasing globally, but the etiology of IBD is still not fully understood. Some, but not all studies find that vitamin D has both protective and therapeutic effects on IBD. To our knowledge, no other study has investigated prenatal exposure to extra vitamin D from either fortified food, diet or supplements in relation to IBD. The aim of this study was to investigate whether a small extra dose of vitamin D from fortification during gestation, was associated with a lower risk of developing IBD in the offspring. Methods: In 1985 mandatory fortification of margarine with vitamin D in Denmark was canceled. To investigate the effect of this policy change we selected all individuals from 2 full year birth cohorts before and after the termination of the mandatory fortification. All individuals were followed for 30 years. By merging data from the Medical Birth Registry with the Danish National Patient Registry, we identified individuals with IBD. Results: 217, 249 individuals were included in the analysis. 875 among the exposed and 1102 among the unexposed fulfilled the criteria for being diagnosed with IBD. A lower odds ratio OR = 0.867 (95% CI: 0.792;0.947) for IBD was observed among those who had been exposed to extra vitamin D from fortified margarine during gestation, compared to those who had not been exposed. The analysis was adjusted for sex and season of birth, but results were essentially similar before and after this adjustment. Conclusions: This study shows, that a small extra dose of vitamin D from fortified margarine during gestation may lower the risk of developing IBD in the offspring, until the age of 30. If these results can be replicated, fortification with vitamin D could be recommended to prevent IBD on a public level. Key messages: Prenatal exposure of vitamin D from fortified food could lower the risk of IBD later in life. Fortification with vitamin D even at a relatively low level could have public health benefits.